Disruptions to routine childhood vaccinations in low- and middle-income countries during the COVID-19 pandemic: A systematic review - Cardoso Pinto, Alexandra M.; Ranasinghe, Lasith; Dodd, Peter J.; Budhathoki, Shyam Sundar; Seddon, James A.; Whittaker, Elizabeth (Frontiers in Pediatrics, 2022)
Background The COVID-19 pandemic has disrupted routine childhood vaccinations worldwide with low- and middle-income countries (LMICs) most affected. This study aims to quantify levels of disruption to routine vaccinations in LMICs. Methods A systematic review (PROSPERO CRD42021286386) was conducted of MEDLINE, Embase, Global Health, CINAHL, Scopus and MedRxiv, on the 11th of February 2022. Primary research studies published from January 2020 onwards were included if they reported levels of routine paediatric vaccinations before and after March 2020. Study appraisal was performed using NHLBI tool for cross-sectional studies. Levels of disruption were summarised using medians and interquartile ranges. Results A total of 39 cross-sectional studies were identified. These showed an overall relative median decline of 10.8% (interquartile range [IQR] -27.6%, -1.4%) across all vaccines. Upper-middle-income countries (upper-MICs) (-14.3%; IQR -24.3%, -2.4%) and lower-MICs (-18.0%; IQR 48.6%, 4.1%) showed greater declines than low-income countries (-3.1%; IQR -12.8%, 2.9%), as did vaccines administered at birth (-11.8%; IQR -27.7%, -3.5%) compared to those given after birth (-8.0%; IQR -28.6%, -0.4%). Declines during the first three months of the pandemic ( 8.1%; IQR -35.1%, -1.4%) were greater than during the remainder of 2020 (-3.9%; IQR 13.0%, 11.4%) compared to baseline. Conclusion There has been a decline in routine paediatric vaccination, greatest in MICs and for vaccines administered at birth. Nations must prioritise catch-up programmes alongside public health messaging to encourage vaccine uptake.